The interconnected relationships between middle ear bulla size, cavitation defects, and chronic otitis media revealed in a syndromic mouse model - Fons, Juan M.; Milmoe, Natalie J.; Dack, Michael R. G.; Joshi, Leena; Thompson, Hannah; Tucker, Abigail S. (Frontiers in Genetics, 2022)
High incidence of chronic otitis media is associated with human craniofacial syndromes, suggesting that defects in the formation of the middle ear and associated structures can have a knock-on effect on susceptibility to middle ear inflammation. Patients with Branchio-Oto-Renal (BOR) syndrome have several defects in the ear leading to both sensorineural and conductive hearing loss, including otitis media. 40% of cases of BOR syndrome are due to haploinsufficiency for EYA1, with mouse models with loss of Eya1 mimicking many of the defects found in patients. Here we characterise the onset, consequences, and underlying causes of chronic otitis media in Eya1 heterozygous mice. Cavitation defects were evident in these mice from Postnatal day (P)11 onwards, with mesenchyme around the promontory and attic regions of the middle ear space. This mesenchyme was still prominent in adult Eya1 Heterozygous mice, while wild-type littermates had fully aerated ears from P14 onwards. microCT analysis highlighted a significantly smaller bulla, confirming the link between bulla size defects and the ability of the mesenchyme to successfully retract. Otitis media was observed from P14, often presenting unilaterally, resulting in hyperplasia of the middle ear mucosa, expansion of secretory cells, defects in the motile cilia, and changes in basal epithelial cell markers. A high incidence of otitis media was identified in older mice but only associated with ears with retained mesenchyme. To understand the impact of the environment, the mouse line was rederived onto a super clean environment. Cavitation defects were still evident at early stages, but these generally resolved over time, and importantly no signs of otitis media were observed at 6 weeks. In conclusion, we show that a small bulla size is closely linked to defects in cavitation and the presence of retained mesenchyme. A delay in retraction of the mesenchyme predates the onset of otitis media, making the ears susceptible to its development. Early exposure to OM appears to exacerbate the cavitation defect, with mesenchyme evident in the middle ear throughout the animal’s life. This highlights that permanent damage to the middle ear can arise as a consequence of the early onset of OM.